AMOURS DU CHEVALIER DE WALBÉ AVEC LA BELLE HORTENSE (1802) O CÓMO LA PROSTITUTA SE HACE MUJER DE VIRTUD: LECTURA TRANSGÉNERO DE UNA DOBLE CONVERSIÓN - Jiménez Salcedo, Juan (Anales de Filología Francesa, 2007)
This article analyses a libertin tale, Amours du chevalier de Walbé avec la belle Hortense, published in 1802 in the collection Les Sérails de Paris. The tale belongs to the libertine tradition of narrations about prostitution, which was quite liked at the 18th century and still exists at the beginning of the 19th century. I will try to make a transgendered reading of two aspects of the tale: Hortense’s lesbianism and Walbé’s transvestism.